THE PROCEDURE OF VERIFYING PRECAUTIONARY MEASURES IN CRIMINAL PROCEEDINGS - Ştefan Alberto LUPU (Challenges of the Knowledge Society)
This paper aims at providing an overview of the institution of precautionary measures also called preliminary injunction measures in the criminal trial, namely of the procedure instituted by the legislator in art. 2502 CPP and on the terms in which the judicial bodies are obliged to verify whether or not the grounds for maintaining precautionary measures still exist. It is a matter of principle that protective measures, like precautionary measures, are measures that have the effect of limiting the fundamental rights of the person against whom they are ordered, and the manner in which they are ordered and maintained must observe the limits and guarantees of the right to a fair trial. The present study will mainly focus on the aspects related to the way in which this procedure is carried out by the judicial bodies, as well as the contradictions encountered in the legal practice on the legal termination of protective measures, on the nature of the terms regulated by art. 2502 CPP and on the conditions that must be analysed in this verification procedure.